Hubungan Jenis Kontainer Dengan Keberadaan Jentik Aedes Aegypti - Tusy Triwahyuni; Ismalia Husna; Devita Febriani; Kukuh Bangsawan (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: To control the mosquito who causes DHF is with controlling the environment first. Which is through controlling the larva's habitat in the water containers. The presence of Aides aegypti larvae in the container is affected by some factors, they are the types of containers and the material of the container. Purpose:To know the relation between types of container with Aedes aegypti in Puskesmas of Way Kandis Bandar Lampung. Method: Using an analytic observational design with a cross-sectional approach. Sampling uses a simple random sampling technique. Conducted by interview method using questionnaire and observation sheet at Puskesmas of Way Kandis Bandar Lampung, then analyze using Spearman test and Chi-Square test. Results: Test result using Spearman is p=0,704, it means there is no relation between types of the container with the presence of Aedes aegypti larvae. Test result using Chi-Square is p=0,639 it means there is no relation between the material of the container with the presence of Aedes aegypti larvae. The test result using Chi-Square is p=0,002 it means there is a significant relationship between the container's lid with the presence of Aedes aegypti larvae. The test result using Chi-Square is p=0,430 it means there is no relation between the number of containers with the presence of Aedes aegypti larvae. Conclusion: Final result suggests that there is no relation between types of a container with the presence of Aedes aegypti larvae, there is no relation between the material of the container with the presence of Aedes aegypti larvae, there is a significant relationship between the container's lid with the presence of Aedes aegypti larvae, And there is no relation between the numbers of containers with the presence of Aedes aegypti larvae.